Correlation of Chemotherapy Frequency with Albumin Levels and Weight Loss in Breast Cancer Patients at Abdoel Wahab Sjahranie Samarinda Regional General Hospital - Salsabilla Halwa; Joko Sapto Pramono; Sepsina Reski (PT FORMOSA CENDEKIA GLOBAL, 2023)
East Kalimantan is ranked 2nd highest in breast cancer in Indonesia. One of the cancer treatments is chemotherapy. Chemotherapy causes effects such as nausea and vomiting and hematological toxicity. Nausea and vomiting are the main factors causing weight loss, and hematological toxicity is the main factor causing hypoalbuminemia. This study aims to determine the relationship between chemotherapy frequency and albumin levels and weight loss in breast cancer patients. The research was conducted in September 2023. There were 33 respondents. The instruments used are digital scales and medical records. Data analysis used the chi-square test (α<0.050). The results of the study showed that there was no relationship between the frequency of chemotherapy and albumin levels (p=0.084) and there was a relationship between the frequency of chemotherapy and weight loss (p=0.030) with a fairly strong relationship (r=0.441).